Dynamic local metrics changes in patients with toothache: A resting-state functional magnetic resonance imaging study - Wang, Mengting; Tang, Xin; Li, Bin; Wan, Tianyi; Zhu, Xuechao; Zhu, Yuping; Lai, Xunfu; He, Yulin; Xia, Guojin (Frontiers in Neurology, 2022)
Objective:The dynamics of local metrics at rest in patients with toothache (TA, Toothache) were studied in the hope of further understanding the altered central neural mechanisms in TA patients. Methods: 30 patients with TA and 30 matched healthy (HC) control volunteers were recruited, and resting-state functional magnetic resonance (rs-MRI) scans were performed on all subjects, and data were analyzed to compare group differences in three dynamic local indices: dynamic regional homogeneity（dReHO）、dynamic low-frequency fluctuation amplitude(dALFF) and dynamic fractional low-frequency fluctuation amplitude(dfALFF). In addition, the association between dynamic local metrics in different brain regions of TA patients and scores on the Visual Analog Scale (VAS) and the Hospital Anxiety and Depression Scale (HADS) were investigated by Pearson correlation analysis. Results: In this study, we found that The local metrics of TA patients changed with time。 Compared with the HC group, TA patients had increased dReHo values in the bilateral middle frontal gyrus, right superior frontal gyrus, middle temporal gyrus, postcentral gyrus, and left superior temporal gyrus left precentral gyrus, precuneus, and angular gyrus, increased dALFf values in the right superior frontal gyrus, and increased dfALFF values in the right middle temporal gyrus, middle frontal gyrus and superior occipital gyrus. (p < 0.01, cluster level P < 0.05). Pearson correlation analysis showed that dReHo values of the left precuneus and left angular gyrus were positively correlated with VAS scores in the TA group. dReHo value of right posterior central gyrus was positively correlated with the HADS score (P < 0.05). Conclusion: There are differences in the patterns of neural activity changes in resting areas of TA patients and the dynamic local metrics may serve as a new neuroimaging biomarker for studying TA and help to reveal the underlying neuropathic mechanisms.